Comparison analysis of PD-1/PD-L1 inhibitors plus lenvatinib or gemcitabine/cisplatin as first-line treatment for patients with advanced intrahepatic cholangiocarcinoma - Huang, Jia-Xin; Liu, Bo; Li, Yu; Li, Xi; Ding, Li-Juan; Wang, Nan-Ya (Frontiers in Oncology, 2023)
Background: Intrahepatic cholangiocarcinoma (ICC) is a highly aggressive primary liver cancer, with incidence increasing worldwide. Effective first-line treatments for advanced ICC patients are currently limited. Therefore, our study aimed to assess the efficacy and safety of programmed death-1(PD-1)/programmed death-ligand 1(PD-L1) inhibitors in combination with gemcitabine/cisplatin (GC) and lenvatinib as first-line treatment in advanced ICC patients. Methods: This retrospective cohort study totally included 51 advanced ICC patients, among whom 25 patients administrated PD-1/PD-L1 plus lenvatinib and 26 patients administrated PD-1/PD-L1 plus GC. Baseline characteristics including demographic information, history of medical, clinical characteristic, laboratory data and imaging examination were collected. The primary endpoints were progression-free survival (PFS), sixth and ninth month overall survival (OS) rate. Survival curve was plotted by Kaplan-Meier method. A Cox proportion risk model was performed to investigate independent risk factors of PFS and OS. The secondary outcomes were objective response rate (ORR), disease control rate (DCR) and adverse events. Results: The median age of advanced ICC patients in our study was 58.0 (95% confidence interval [95% CI] =48.0-72.4) years, with 33 males and 18 females. Patients in PD-1/PD-L1 inhibitors plus lenvatinib group were more likely to be in ECOG grade above 1, develop ascites and have an elevated level of ALT. The ORR was 16.0% in PD-1/PD-L1 inhibitors plus lenvatinib group and 23.1% in GC group (P=0.777). The DCR was 52.0% in lenvatinib group and 46.2% in GC group (P=0.676). The combination treatment of PD-1/PD-L1 inhibitors plus lenvatinib was associated with longer PFS than GC group, however, it was not statistically significant (lenvatinib: 9.5 months, GC: 5.1 months, P=0.454). The 6th-month and 9th-month OS rate were 82.0% and 76.9% in lenvatinib group and 87.4% and 71.5% in GC group. After adjusting for confounders, multivariate Cox regression analysis showed ECOG grade above 1 was independent risk factor for PFS (hazard ratio [HR]=3.388, 95%CI=1.312-8.746, P=0.012) and OS (HR=4.220, 95%CI=1.131-15.742, P=0.032). Conclusion: PD-1/PD-L1 inhibitors in combination with lenvatinib or GC all demonstrated significant efficacy and safety as first-line treatment in patients with advanced ICC. As for patients who refuse or intolerance to chemotherapy, PD-1/PD-L1 plus lenvatinib would be recommended.